The sensitivity of rice production to transplanting date and irrigation water management in a drier climate future scenario - Yiwen, Mok; Zulkafli, Zed; Raffar, Nurfarhana; Mohamed Rehan, Balqis; Nurulhuda, Khairudin; Chung, Jing Xiang; Tangang, Fredolin (Springer Science and Business Media Deutschland GmbH, 2025)
Climate change impacts on water availability and rice production, combined with growing human population, is an existing threat to global food security. In this research, the potential impacts of climate change on the water balance and rice yield were assessed with the baseline period (1986–2005) to the future period (2015–2094) in a rice planting region within the Muda Irrigation Scheme area, Malaysia. A hydrological model was used to project the changes of water components and rice yield production in response to a drying future climate scenario, in which the seasonal temperature is projected to increase while seasonal precipitation is projected to decrease. Next, two adaptation strategies (1) shifting planting dates and (2) adding supplementary irrigation were evaluated for their mitigating effects. Results found a reduction in evapotranspiration, irrigation, surface runoff, and rice yield were observed for both seasons under climate change, relative to the baseline scenario. Next, under both adaptation strategies, results show changes in the water balance that compensate for the loss in yield production. Specifically, delayed planting contributed to positive improvement of evapotranspiration, irrigation, and percolation. Meanwhile, increasing supplementary irrigation led to enhancement in most water components, except surface runoff.